Handbook of family policies across the globe - Robila, Mihaela (Springer New York, 2014)
Family policy holds a particular status in the quest for a more equitable world as it intersects the rights of women, children, and workers. But despite local and global efforts and initiatives, the state of family policy in different areas of the world varies widely. Through a cross-section of countries on six continents, Family Policies Across the Globe offers the current state of the laws concerning family life, structure, and services, providing historical, cultural, and socioeconomic context. Lucidly written chapters analyze key aspects of family definition, marriage, child well-being, work/family balance, and family assistance, reviewing underlying social issues and controversies as they exist in each country. Details of challenges to implementation and methods of evaluating policy outcomes bring practical realities into sharp focus, and each chapter concludes with recommendations for improvement at the research, service, and governmental levels. The result is an important comparative look at how governments support families, and how societies perceive themselves as they evolve. Among the issues covered: Sierra Leone: toward sustainable family policies. Russia: folkways versus state-ways. Japan: policy responses to a declining population. Australia: reform, revolutions, and lingering effects. Canada: a patchwork policy. Colombia: a focus on policies for vulnerable families. Researchers, professors and graduate students in the fields of social policy, child and family studies, psychology, sociology, and social work will find in Family Policies Across the Globe a reference that will grow in importance as world events continue to develop.